REVIEW: TINGKAT KESESUAIAN PENULISAN RESEP SESUAI FORMULARIUM RUMAH SAKIT - Rachmawati, Ita; Hermanto, Faizal (Jurnal Abdimas Bina Bangsa, 2024)
The hospital formulary is a list of drugs compiled by the Pharmacy and Therapy Team (TFT) and agreed upon by the medical staff and refers to the national formulary, which is determined and enforced by the hospital leadership. Discrepancies in drug prescriptions with the hospital formulary can result in a decrease in the quality of hospital services and inefficient costs used. This research aims to determine the percentage of prescriptions discrepancies with the hospital formulary. This research uses a narrative review method, namely by using articles or journals that were published in 2013-2023, a literature search was carried out on Pubmed and Google Scholar. The literature obtained was from 11 journals and was included in the inclusion criteria. The results obtained indicate that the percentage of conformity between prescription writing and the formulary has not reached 100%. This shows that the suitability of prescribing has not reached the minimum one hundred percent service standard set by the government